Estimación del potencial de producción de un pozo horizontal posfracturado hidráulicamente en formación de shale gas con aplicación geo-mecánica (2015)
The shale reservoirs are affected by the in situ stresses, which have influence in the loss of the permeabilit Y of natural fractures and the rock matrix. This is due to the compaction of the formation, thanks to the production of fluids. For this reason, in this paper was determined the impact of geo-mechanics on the productivity of a horizontal well hydraulically fractured in a shale gas formation, by coupling the flow model and the model of the rock deformation using a reservoir simulator.